KESADARAN GENDER YANG ISLAMI - Nurdeni Dahri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
Biological differences between men and women have in the implementation of social and cultural life. There has been a gender gap due to the multiplicity of interpretations of the notion of gender itself. In-depth research is needed to determine the cause of the gap, let alone Islam declared the doctrine that leads to gender bias. Based on the discussion in this paper is declared Gender division of roles and responsibilities between women and men as a result of socio-cultural construction of society, which can be changed according to the demands of the changing times. While sex (gender: male and female) are not changed and the nature of God. In the teachings of Islam there is no difference between women and men in all its aspects, distinguishing only charity and piety